Technology Driven Transformation Education System Using Digitalization: A Study of Makawanpur District, Nepal - Chhetri, Raju; Parajuli, Shivaraj; Manandhar, Dev Ratna; Basnet, Sanjay Kumar; Thapa, Bibash; Regmi, Suresh; Humagain, Sumargi (A Peer Reviewed Journal on Social Sciences, 2024)
Modern education is transforming knowledge through digitalization. Nepalese changing from traditional to advanced learning. This study aims to find recent practices of education, and digital uses applicability in daily life among management students of college levels. Purposively, the public and private colleges of Makwanpur-Bagamati province were chosen. 44 students (22 each from public and private) of higher secondary to Bachelor degree level were set online questions using Google sheet (2024). Interviews (KII and consultative) were performed with IT experts, and admin-officials using the Google Meet program. Results demonstrated digitalization helped students in transformative learning essential devices supported through colleges. Facilities and modern devices are found high in private and learning is noticed high by scholars of public colleges. Uses of AI are limited, E-wallet and manual cash transfers are average in the daily lives of surveyed respondents. The bank account users and overall digitalization practice were found satisfactory. Digitalization helps to become smart in learning among the students and much familiar with use. Policymakers and management can support making digital through policies that provides digital platforms for eminence education.